Effects of auxin and cytokinin levels on the success of air layering in tea plant clones of GMB 7 and GMB 9 using husk charcoal, cocopeat and moss media - Widyastuti, Ika Betty; Yudono, Prapto; Putra, Eka Tarwaca Susila (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2020)
The research aimed to propagate tea plants by air layering in order to obtain new plants with shorter immature plants period (TBM), which is 1.5 years, by utilizing wasted branches from routine clean pruning activities in tea plantations. The research was conducted from August 2018 to January 2019 at tea plantation of PT. Pagilaran, Batang, Central Java. Experiment using single factor treatment was arranged in a Completely Randomized Design with three replications. The treatment was layering media, consisting of husk charcoal, moss, and cocopeat, which were applied on GMB 7 and GMB 9 clones. The results showed significant effects of the layering media on the levels of auxin and cytokinin in GMB 7. The highest levels were found in the husk charcoal and moss media. Analysis of sucrose, glucose and total sugar as well as the physiological analysis of the air layering roots showed no significant difference in the fresh weight, dry weight, volume, surface area, diameter, and length of the roots. Husk charcoal resulted in the highest success rate of the air layering in GMB 7, which was 100%. Meanwhile, GMB 9 showed significant difference only in the auxin levels. There was no significant effect of layering media on the analysis of sucrose, glucose and total sugar as well as on the physiological analysis of the air layering roots. Both husk charcoal and moss media resulted in the highest success rate of the air layering in GMB 9, which was 58.33%.Â Â Â